Wabanaki Experiences and Perspectives on “Our Shared Ocean”: Maine Indian Tribal-State Commission Special Report Sea Run - Sutton, Anthony; Esty-Kendall, Judson; Thibeault, Paul (Maine Policy Review, 2023)
The Maine Indian State Tribal Commission (MITSC) recently published a special report titled, Sea Run, documenting the impact of Colonial and Maine policies and activities on the quality and quantity of tribal fisheries spanning the time from first contact between Europeans and the Wabanaki Nations to today.